2013
DOI: 10.1080/02701367.2013.762286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uncertainty on the Reaction Response in Fencing

Abstract: Purpose: The objective was to determine the way in which the level of uncertainty produced during the execution of al unge attack with target change (two or four possible responses) affects reaction-response time parameters and kinematic factors involved in the technical coordination of the attack. Method: Seventeen fencers from the Spanish National Men's Fencing Team participated in the study, which involved performing alunge attack against a moving circle as fast as possible, while attempting to place the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 11 publications
5
23
3
Order By: Relevance
“…Take-off time (tt) was similar in both techniques and oscillated around 0.5 s. A significant difference, however, was observed in VCoG in the lunge, for which Vmax oscillated between 1.8 and 2.3 m/s. Similar results (1.36-2.08 m/s) were obtained for the direct-thrust attack by Gutierrez-Davila et al [12,13]. On the other hand, the values of the fleche velocity were in the range between 2.6 and 2.9 m/s.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Take-off time (tt) was similar in both techniques and oscillated around 0.5 s. A significant difference, however, was observed in VCoG in the lunge, for which Vmax oscillated between 1.8 and 2.3 m/s. Similar results (1.36-2.08 m/s) were obtained for the direct-thrust attack by Gutierrez-Davila et al [12,13]. On the other hand, the values of the fleche velocity were in the range between 2.6 and 2.9 m/s.…”
Section: Discussionsupporting
confidence: 87%
“…They concluded that perpendicular foot placement with the front foot pointing forward is the optimum position for achieving peak power and velocity of the body during a lunge. Other researchers have discussed the significance of the timing parameters of the reaction response time (RRT) in the fencer's efficiency [4,12,13]. They found that the relationship between the RRT and the kinematic parameters of a lunge depends on target change [15].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, TCT (tx) (x=0,..,4) for each player was deined as x/5 MT + RT (being MT, RT median values of such player. his result contradicts the hypothesis of previous studies that uncertainty resulting from target change increases movement time (Borysiuk & Waskiewicz, 2008;Gutiérrez-Dávila et al, 2013;Sanderson, 1983).…”
Section: Contrastcontrasting
confidence: 57%
“…The most frequently blood indices used for detection biological responses to an athletic competition or the other psychophysical stimuli are blood levels of steroidal hormones cortisol (C), testosterone (T) and so-called anabolic-catabolic in - Fencing belong to that sport family, which required from a contestant mostly good special orientation, time response, visual search ability, movement accuracy and explosive strength of lower limbs. Indeed, these fencers` attributes have been examines extensively [6][7][8][9][10][11][12][13], while biological cost of a fencing tournament, which usually lasts the whole day is poorly explored. This study was aimed to explore biological cost of participation in a one-day fencing tournament based on study of the behaviors of blood cortisol, testosterone, lactate (LA) creatine kinase (CK), and state anxiety, mood state and physical well-being throughout the entire competition.…”
Section: Introductionmentioning
confidence: 99%